IMPLEMENTASI PROGRAM PENGELOLAAN SAMPAH PASAR GIWANGAN OLEH DINAS PERDAGANGAN KOTA YOGYAKARTA - I Kadek Hendrawan; Ardiyati (Halu Oleo University, 2025)
The study aims to (1) Find out how the implementation of the Giwangan market waste management program in Yogyakarta City. (2) To find out what challenges and problems are faced during the implementation process of the Giwangan market waste management policy. This research method uses a descriptive qualitative research method. The results of the study show that waste management in Yogyakarta City already has policy standards regulated in Regional Regulation Number 1 of 2022, but its implementation still requires optimization in budget allocation, personnel training, and infrastructure. Cooperation with related organizations, such as the Environmental Service, needs to be strengthened to increase program effectiveness. In addition, the involvement of implementers who have special expertise is an important factor in the success of this policy. The Trade Service must also pay attention to the economic, social, and political conditions that influence waste management policies and continue to encourage positive attitudes and active participation of implementers to achieve the goal of market sustainability.